Manufacturing-as-a-Service—From e-Work and Service-Oriented Architecture to the Cloud Manufacturing Paradigm. Issue 3 (2015) - Moghaddam, Mohsen; Silva, José Reinaldo; Nof, Shimon Y.
Abstract: After consolidation of classic manufacturing line, several alternative arrangements have been experimented and modeled to explore emerging features such as non-linearity, integration, flexibility, and decentralization by the virtue of holonic and agent-based technologies. All this transformation reflects remarkable evolution in manufacturing systems and emergence of a ubiquitous culture introduced by e- Work and supported by Information and Communication Technologies (ICT). Yet, there is a new paradigm shift emerging in manufacturing: the tendency to move from the traditional product- /production-oriented manufacturing to service-oriented manufacturing. Such tendency is being spread in academic work as well as in today's management decisions. This article briefly reviews and analyzes the emerging coalition between collaborative e-Manufacturing and Service-Oriented Architecture (SOA) towards the fonnation of a new manufacturing paradigm composed of a cloud of sendees that enable the notion of Manufacturing-as-a-Service (MaaS).